Left Ventricular Diastolic Performance at Rest in Patients with Angina and Normal Systolic Function - Assessment by Equilibrium Radionuclide Angiography - Maini, C. L.; Incalzi, R. Antonelli; Bonetti, M. G.; Valle, G.; Montenero, A. S. (Nuklearmedizin - NuclearMedicine, 1985)
The aim of the study was to correlate diastolic function, as evaluated by peak filling rate (PFR) and relative time (TPFR), with the severity of ischemic heart disease, as evaluated by exercise electrocardiography. Accordingly, 83 ischemic patients with effort angina, but normal ejection function at rest and normal left ventricular size, were studied by equilibrium radionuclide angiocardiography within two weeks from the exercise ECG. Diastolic dysfunction, as determined from PFR and, to a lesser extent, from TPFR, is common in patients with ischemic heart disease and normal systolic function. The prevalence and severity of such dysfunction is related more to the severity of the ischemia, as evaluated by the exercise ECG, than to the presence of an old myocardial infarction. Such findings are consistent with the hypothesis that PFR reflects mainly the early diastolic active uncoupling process.